Electron Beam Processing of Materials - Vutova, Katia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue reprint presents articles from researchers working on materials processing via electron beams as well as on their characterization, properties, and applications. The articles presented cover various topics, including metal melting and welding, additive manufacturing, electron beam irradiation, electron beam lithography, process modeling, etc.